Implementation of Carbon Emission Disclosure (CED) in Hydroelectric Power Plants in the Sumatra Region - Rafiqah Humaira; M Afif Herliandi Nasution; Elina R. Gustarina (CV Edujavare Publishing, 2026)
Hydroelectric Power Plants (PLTA) are often categorized as clean energy, but scientific literature shows that hydroelectric power plants, especially reservoir based ones in tropical regions have the potential to produce significant greenhouse gas (GHG) emissions through submerged biomass decomposition, infrastructure construction, and long-term operation and maintenance. This study aims to calculate carbon emissions based on Life Cycle Assessment (LCA) at five hydroelectric power plants in the Sumatra region (Singkarak, Maninjau, Koto Panjang, Asahan 1, and Batang Agam), assess the existing condition of Carbon Emission Disclosure (CED) practices, and design an integrated CED implementation model with a Measurement, Reporting, and Verification (MRV) framework. The approach used is quantitative-descriptive with cradle-to-grave system limits according to ISO 14040/14044, using a functional unit of 1 kWh of electricity generated. The results show that the life cycle emission intensity of the five hydropower plants ranges from 33.7 to 85.3 g CO₂e/kWh with a weighted average of 52.4 g CO₂e/kWh more than double the global median of 24 g CO₂e/kWh for hydropower plants. Reservoir emissions (CH₄ and CO₂ decomposition) account for 38–67% of total emissions at reservoir-type hydropower plants, making them a hotspot for underreported emissions. The existing CED assessment showed an average CED Index of 0.32 (scale 0–1), well below the “adequate” threshold (≥0.70), indicating that none of the sampled hydropower plants have an integrated and verified emissions disclosure system. The developed CED-MRV model was successfully validated on 4 out of 5 hydropower plants (80%), exceeding the 70% target, and is recommended as a standard for replication for other hydropower plants in Sumatra.